2022
DOI: 10.3389/fnins.2022.1003145
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap of axonal regeneration in the central nervous system: A state of the art review on central axonal regeneration

Abstract: Neuronal regeneration in the central nervous system (CNS) is an important field of research with relevance to all types of neuronal injuries, including neurodegenerative diseases. The glial scar is a result of the astrocyte response to CNS injury. It is made up of many components creating a complex environment in which astrocytes play various key roles. The glial scar is heterogeneous, diverse and its composition depends upon the injury type and location. The heterogeneity of the glial scar observed in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 214 publications
0
4
0
Order By: Relevance
“…Both beneficial and detrimental roles have been attributed to the glial scar and reactive astrocytes (reviewed in Ding et al (2021) ). Among the detrimental roles is the impediment of axonal regrowth, partly due to the release of inhibitory factors by reactive astrocytes [reviewed in Costa et al (2022)] . Astrocyte activation and astrogliosis are paralleled by increased GFAP expression.…”
Section: Resultsmentioning
confidence: 99%
“…Both beneficial and detrimental roles have been attributed to the glial scar and reactive astrocytes (reviewed in Ding et al (2021) ). Among the detrimental roles is the impediment of axonal regrowth, partly due to the release of inhibitory factors by reactive astrocytes [reviewed in Costa et al (2022)] . Astrocyte activation and astrogliosis are paralleled by increased GFAP expression.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-based therapies have shown great promise by targeting damaged axonal pathways. Still, the strategies proposed are not designed to restore long-distance axons; novel strategies enhance axons’ intrinsic ability to regenerate and create a permissive environment for axonal outgrowth [ 8 , 62 , 63 ]. Transplantable “scaffolds” have recently been used to facilitate axon regeneration.…”
Section: The Nervous Systemmentioning
confidence: 99%
“…Localization of reactive astrocytes that display changed morphology depends on the proximity to the insult. Studies have shown that astrocytes close to the injury site have shown greater elongation of processes as compared to astrocytes that are localized further away from the injury site [240].…”
Section: Differences In Localization Age and The Type Of Injurymentioning
confidence: 99%